Highly efficient decomposition of toluene using a high-temperature plasma-catalysis reactor. (May 2020) - Yao, Shuiliang; Chen, Zhizong; Xie, Han; Yuan, Yuchen; Zhou, Ruowen; Xu, Bingqing; Chen, Junxia; Wu, Xinyue; Wu, Zuliang; Jiang, Boqiong; Tang, Xiujuan; Lu, Hao; et al.
Abstract: Plasma-catalysis technologies (PCTs) have the potential to control the emissions of volatile organic compounds, although their low-energy efficiency is a bottleneck for their practical applications. A plasma-catalyst reactor filled with a CeO2 /γ-Al2 O3 catalyst was developed to decompose toluene with a high-energy efficiency enhanced by the elevating reaction temperature. When the reaction temperature was raised from 50 °C to 250 °C, toluene conversion dramatically increased from 45.3% to 95.5% and the energy efficiency increased from 53.5 g/kWh to 113.0 g/kWh. Conversely, the toluene conversion using a thermal catalysis technology (TCT) exhibited a maximum of 16.7%. The activation energy of toluene decomposition using PCTs is 14.0 kJ/mol, which is far lower than those of toluene decomposition using TCTs, which implies that toluene decomposition using PCT differs from that using TCT. The experimental results revealed that the Ce 3+ /Ce 4+ ratio decreased and Oads /Olatt ratio increased after the 40-h evaluation experiment, suggesting that CeO2 promoted the formation of the reactive oxygen species that is beneficial for toluene decomposition. Highlights: Toluene decomposition using a plasma-catalysis technology (PCT) was investigated. Energy efficiency was improved to 113.0 g/kWh by elevating reaction temperature. Toluene conversion was 95.5% using PCT, but 16.7% using thermal catalysis technology. Activation energy of toluene decomposition is 14.0 kJ/mol. CeO2 promoted the formation of reactive oxygen species on CeO2 surface.